Anti-HIV-1 activity of flavonoid myricetin on HIV-1 infection in a dual-chamber in vitro model. - Silvana Pasetto (PLoS ONE, 2014)
HIV infection by sexual transmission remains an enormous global health concern. More than 1 million new infections among women occur annually. Microbicides represent a promising prevention strategy that women can easily control. Among emerging therapies, natural small molecules such as flavonoids are an important source of new active substances. In this study we report the in vitro cytotoxicity and anti-HIV-1 and microbicide activity of the following flavonoids: Myricetin, Quercetin and Pinocembrin. Cytotoxicity tests were conducted on TZM-bl, HeLa, PBMC, and H9 cell cultures using 0.01-100 µM concentrations. Myricetin presented the lowest toxic effect, with Quercetin and Pinocembrin relatively more toxic. The anti-HIV-1 activity was tested with TZM-bl cell plus HIV-1 BaL (R5 tropic), H9 and PBMC cells plus HIV-1 MN (X4 tropic), and the dual tropic (X4R5) HIV-1 89.6. All flavonoids showed anti-HIV activity, although Myricetin was more effective than Quercetin or Pinocembrin. In TZM-bl cells, Myricetin inhibited ≥90% of HIV-1 BaL infection. The results were confirmed by quantification of HIV-1 p24 antigen in supernatant from H9 and PBMC cells following flavonoid treatment. In H9 and PBMC cells infected by HIV-1 MN and HIV-1 89.6, Myricetin showed more than 80% anti-HIV activity. Quercetin and Pinocembrin presented modest anti-HIV activity in all experiments. Myricetin activity was tested against HIV-RT and inhibited the enzyme by 49%. Microbicide activities were evaluated using a dual-chamber female genital tract model. In the in vitro microbicide activity model, Myricetin showed promising results against different strains of HIV-1 while also showing insignificant cytotoxic effects. Further studies of Myricetin should be performed to identify its molecular targets in order to provide a solid biological foundation for translational research.